Media Exposure and Internal Migration - Evidence from Indonesia - Lídia Farré; Francesco Fasani (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
This paper investigates the impact of television on internal migration in Indonesia. We exploit the differential introduction of private television throughout the country and the variation in signal reception due to topography to estimate the causal effect of media exposure. Our estimates reveal important long and short run effects. An increase of one standard deviation in the number of private TV channels received in the area of residence reduces future inter- provincial migration by 1.7-2.7 percentage points, and all migration (inter and intra- provincial) by 4-7.4 percentage points. Short run effects are slightly smaller, but still sizeable and statistically significant. We also show that respondents less exposed to private TV are more likely to consider themselves among the poorest groups of the society. As we discuss in a stylized model of migration choice under imperfect information, these findings are consistent with Indonesia citizens over-estimating the net gains from internal migration.
Keywords: J61; L82; O15; 330; Information; Migration decisions; Television